INVESTMENT CREDIT ANALYSIS BY ECONOMIC SECTOR IN INDONESIA - Afrizal, Ardi; Nurdin, Nurdin; Halim, Abd (Jurnal Development, 2021)
The purpose of this study is to analyze investment credit by economic sector in Indonesia through a simple linear regression model through the Least Squares (NLS and ARMA) approach. The findings show that the effect of interest rates on investment credit is not significant 0.334 with a R2 value of 1.06%. Meanwhile, the effect of inflation on investment credit is very significant 0.0021 with R2 of 10.31 %%. Then for the effect of investment credit on economic growth is not significant 0.654 or with an R2 value of 0.0023. Meanwhile, the effect of investment credit on formal employment is very significant 0.0033 with a R2 value of 9.5%. The results of the research findings recommend an evaluation of monetary policy carried out by the government, especially the stability of interest rates on investment credit and economic growth in Indonesia.